Is there a Regional Difference in Symptoms Perception Associated with pre- Menstrual Syndrome? Results from a National Study among reproductive-Age Women in Brazil (Global Journal of Medical Research, 2022)
Background Evaluate the prevalence intensity and regional distribution of premenstrual syndrome PMS symptoms reported by reproductive age Brazilian women Methods An observational and retrospective study was conducted analyzing data of women from the five Brazilian regions Women aged 20 to 49 years who consulted at private healthcare services filled up a self-reported questionnaire about the prevalence and intensity of somatic and psychoemotional pre-menstrual symptoms Results A total of 23104 women stated to have premenstrual symptoms of which 38 91 n 8990 reported that these symptoms cause functional impairment
Keywords: premenstrual syndrome; Brazilian women; regional study; premenstrual severity symptoms